Association between patient satisfaction and motivation of health care personnel in a neurosurgery hospitalization service of a specialized institute - Saavedra Ramírez, Luis (2022)
Objective: To determine if there is an association between level of patient satisfactions and motivation of health care personnel in a neurosurgery hospitalization service of a specialized institute. Methods: Cross-sectional study conducted at the neurosurgical services of Instituto Nacional de Ciencias Neurológicas from July to October 2016. Two questionnaires were applied, SERVQUAL to evaluate patient satisfaction and a questionnaire following the Herzberg’ s theory to evaluate motivation of health care personnel. Chi square with Yates correction was used to test associations. Results: Results in parenthesis are shown on patient satisfaction for medical evaluation (97%),  medical approach (95%), interest of physicians on well-being of patients (94%), interest of nurses on well-being of patients (91%), while level of motivation of health care personnel on having an interesting job (98%), agreement on learning new stuff (96%) and having a job to bring good care for patients was (90%). An association between level of patient satisfaction and level of health care personnel was found OR: 4.22 IC 95% 1.44-12.33. Conclusions: An association between level of patient satisfaction and level of health care personnel was found.